Hadis Akhlak dan Filsafat Etika Taha Abdurrahman: Kritik Modernitas dan Tawaran Alternatif: Taha Abdurrahman’s Moral Hadith and Ethics: Critique of Modernity and its Alternatives - Nurul Ihsannudin (UIN Sunan Kalijaga Yogyakarta, 2023)
The rate of development of science and information technology experienced by humans, more or less, leads them to rapid and instant life changes. Modernity with all the conveniences offered in it has an impact on humans, both positive and negative. However, modernity dissolves humans in conditions of social, economic and political inequality. Colonialism and imperialism are part of the many consequences of modernity. Seeing the phenomenon of life, Taha Abdurrahman, a Muslim thinker and philosopher from Morocco, conducted an in-depth study of the issue of modernity and modern human behavior with the provisions of the hadith akhlak that was said by the Prophet Muhammad. So this study tries to reveal (a) how relevant the hadith akhlak and ethical philosophy of Taha Abdurrahma; (b) what are the criticisms conveyed by Taha on the reality of modernity; and (c) what alternative offers for modernity according to Taha. This library research finds that there is a relevance and strong role of the hadith akhlak on the ethical philosophy of Taha. He critiqued the rationalism on which Western modernity was based. He also offers a spirit of modernity which is based on al-rusyd, al-naqdÄ« and al-syumÅ«l. Keywords :Â Ethics, Hadith Akhlak, Modernity Criticism, Taha Abdurrahman.